A "short-cut" response of autophagy to oxidative stress: oxygen-dependent activity of a lysine demethylase guides the activity of ULK1 during hypoxia. Issue 8 (3rd August 2022) - Yu, Ge; Klionsky, Daniel J.
ABSTRACT: Hypoxia is a type of stress caused by an insufficient supply of oxygen. Macroautophagy/autophagy, a well-conserved pathway, is induced during hypoxia; however, the exact mechanism by which autophagy is regulated in a hypoxic environment remains to be elucidated. A recent study by Li et al. shed light on how hypoxia can regulate early steps of autophagy induction. In this study, the authors discovered a novel symmetrical dimethylation of ULK1 at arginine 170 (R170me2s) that accumulates during hypoxia and increases ULK1 kinase activity by promoting autophosphorylation of ULK1 at T180. The authors identified PRMT5 and KDM5C as the primary methyltransferase and demethylase regulating ULK1 R170me2s and show that the lack of oxygen directly leads to reduced activity of KDM5C, which is likely the cause of accumulation of ULK1 R170me2s during hypoxia. Furthermore, the authors showed that ULK1 R170me2s promotes mitochondrial turnover and maintains cell viability in response to hypoxia stress. Together these data provide a new perspective on how the oxygen level regulates autophagy induction and show the physiological role of ULK1 R170me2s.